2012
DOI: 10.1021/jm201657x
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Active Site Inhibitors of the Human Farnesyl Pyrophosphate Synthase: Apoptosis and Inhibition of ERK Phosphorylation in Multiple Myeloma Cells

Abstract: Human farnesyl pyrophosphate synthase (hFPPS) controls intracellular levels of FPP and post-translational prenylation of small GTPase proteins, which are essential for cell signaling and cell proliferation. Clinical investigations provide evidence that N-BP inhibitors of hFPPS are disease modifying agents that improve survival of multiple myeloma (MM) patients via mechanisms unrelated to their skeletal effects. A new series of N-BPs was designed that interact with a larger portion of the GPP subpocket, as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 42 publications
3
48
0
Order By: Relevance
“…Gln171 also facilitates binding of the allylic tail via π-stacking interaction involving its planar side chain, but this residue further contributes to substrate binding by providing a polar contact to the pyrophosphate-Mg 2+ -water cluster. In our work, we have shown that these residues participate in similar interactions with bisphosphonate inhibitors that have extended and rigid lipophilic side chains, such as the aminopyridine inhibitors 8a and 8b (Figure 4B) (De Schutter et al, 2012; Lin et al, 2012), and the thienopyrimidine-based inhibitor 10 (Leung et al, 2013b). …”
Section: Structures Of Prenyl Synthase Enzymes—implications For Drug mentioning
confidence: 69%
See 4 more Smart Citations
“…Gln171 also facilitates binding of the allylic tail via π-stacking interaction involving its planar side chain, but this residue further contributes to substrate binding by providing a polar contact to the pyrophosphate-Mg 2+ -water cluster. In our work, we have shown that these residues participate in similar interactions with bisphosphonate inhibitors that have extended and rigid lipophilic side chains, such as the aminopyridine inhibitors 8a and 8b (Figure 4B) (De Schutter et al, 2012; Lin et al, 2012), and the thienopyrimidine-based inhibitor 10 (Leung et al, 2013b). …”
Section: Structures Of Prenyl Synthase Enzymes—implications For Drug mentioning
confidence: 69%
“…Replacement of the Cα-hydroxyl with a hydrogen (e.g., 2a vs. the corresponding deoxybisphosphonate 2b ) or Cα-halogen substituent (e.g., 2c , d ) has been found to decrease affinity for bone, as well as the potency in inhibiting hFPPS (Marma et al, 2007). Bisphosphonate inhibitors with various heterocyclic lipophilic side chains, including derivatives of zoledronic acid (e.g., 1b , c ) pyridinium deoxybisphosphonates ( 7a–c ) (Zhang et al, 2009), aminopyridines ( 8a–d ) (De Schutter et al, 2012; Lin et al, 2012), azaindoles (Ebetino et al, 2010a,b) and imidazopyridines ( 9a – c , respectively) (Ebetino et al, 2010c), and thienopyrimidines (e.g., 10 ) (Leung et al, 2013a,b) have also been reported.…”
Section: Isoprenoids Fpps/ggpps and Neurodegeneration—the Current Hypmentioning
confidence: 99%
See 3 more Smart Citations